Texting Parents about Early Child Development : Behavioral Changes and Unintended Social Effects - Barrera, Oscar; Macours, Karen; Premand, Patrick; Vakis, Renos (World Bank, Washington, DC, 2020)
Parenting interventions have the potential to improve early childhood development. Text messages are considered a promising channel to deliver parenting information at large scale. This paper tests whether sending text messages about parenting practices impacts early childhood development. Households in rural Nicaragua were randomly assigned to receive messages about nutrition, health, stimulation, or the home environment. The intervention led to significant changes in self-reported parenting practices. However, it did not translate into improvements in children's cognitive development. When local opinion leaders were randomly exposed to the same text message intervention, parental investments declined and children's outcomes deteriorated. Since interactions between parents and leaders about child development also decreased, the negative effects may have resulted from a crowding-out of some local leaders.